Strategies for Strengthening Micro Business Management Through Difficult Times in the Middle of the Covid-19 Pandemic - Siahaan, Elisabet; Aritonang, Evawany Yunita; Siahaan, Rudy H.; Sitepu, Yuni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic that began in March 2020 has shaken the world economy and Indonesia. To reduce transmission that is so fast and deadly, the government implemented a new normal policy of social restrictions that limit people's mobility and carry out activities by implementing health protocols. As a result of the enactment of social restrictions, there is a decrease in consumer purchasing power so that many business actors experience a decrease in turnover to go out of business. This devotion aims to analyze and recommend the right strategies in strengthening micro-businesses to be able to survive in the midst of the Covid-19 pandemic. The methods used are methods of science transfer, guidance, training, and mentoring. There is a change in the understanding of micro-businesses in managing effective human resources. Partners have been able to carry out a healthy, clean, safe and nutritious production process. This devotion also makes financial management partners and systematically registrars the stock of goods and production products. The partner becomes aware of the applicable legal system so as to be able to carry out business activities without breaking the law.